New perspectives in patient education for cardiac surgery using 3D-printing and virtual reality - Grab, Maximilian; Hundertmark, Fabian; Thierfelder, Nikolaus; Fairchild, Matthew; Mela, Petra; Hagl, Christian; Grefen, Linda (Frontiers in Cardiovascular Medicine, 2023)
Background: Preoperative anxiety in cardiac surgery can lead to prolonged hospital stays and negative postoperative outcomes. An improved patient education using 3D models may reduce preoperative anxiety and risks associated with it. Methods: Patient education (PE) was performed with standardized paper-based methods (n=34), 3D-printed models (n=34) or VR (Virtual reality) models (n=31). Anxiety and procedural understanding were evaluated using questionnaires prior to and after PE. Additionally, time spent for PE and overall quality were evaluated among further basic characteristics (age, gender, medical expertise, previous non-cardiac surgery and previously informed patients). Included surgeries were CABG, SAVR and TAA. Results: A significant reduction in VAS anxiety was achieved after PE with VR models (5.00 to 4.32, -0.68, p < 0.001). Procedural knowledge significantly increased for every group after PE while the visualization and satisfaction were best rated for PE with VR. Patients rated the quality of PE using both visualization methods individually (3D and VR models) higher compared to the control group of conventional paper-sheets (control paper-sheets: 86.32 %  11.89 %, 3D: 94.12 %  9.25 %, p < 0.0095, VR: 92.90 %  11.01 %, p < 0.0412). Conclusion: Routine patient education with additional 3D models can significantly improve the patients’ satisfaction and reduce subjective preoperative anxiety effectively.